1997
DOI: 10.1021/bi961971n
|View full text |Cite
|
Sign up to set email alerts
|

Purine Nucleoside Phosphorylase. 3. Reversal of Purine Base Specificity by Site-Directed Mutagenesis

Abstract: Human purine nucleoside phosphorylase (PNP) is highly specific for 6-oxopurine nucleosides with a catalytic efficiency (kcat/KM) for inosine 350000-fold greater than for adenosine. Crystallographic studies identified Asn243 and Glu201 as the residues largely responsible for the substrate specificity. Results from mutagenesis studies demonstrated that the side chains for both residues were also essential for efficient catalysis [Erion, M. D., et al. (1997a) Biochemistry 36, 11725-11734]. Additional mechanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
101
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(126 citation statements)
references
References 25 publications
24
101
0
1
Order By: Relevance
“…3B). Guanosine can therefore be bound more efficiently than inosine by yeast PNP, a situation similar to that reported for human PNP for which the K m s for guanosine and inosine are 12 and 45 M, respectively (17). Finally, the V max and k cat of PNP, with inosine as substrate, were 2.6 M min Ϫ1 and 38 s Ϫ1 , respectively.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…3B). Guanosine can therefore be bound more efficiently than inosine by yeast PNP, a situation similar to that reported for human PNP for which the K m s for guanosine and inosine are 12 and 45 M, respectively (17). Finally, the V max and k cat of PNP, with inosine as substrate, were 2.6 M min Ϫ1 and 38 s Ϫ1 , respectively.…”
supporting
confidence: 79%
“…Finally, the V max and k cat of PNP, with inosine as substrate, were 2.6 M min Ϫ1 and 38 s Ϫ1 , respectively. This latter parameter of the yeast enzyme is therefore similar to the one reported for human PNP and inosine: 57 s Ϫ1 for k cat (17). A pnp1 null mutant (purchased from Euroscarf) did not show any obvious growth defect.…”
supporting
confidence: 77%
“…In addition to differences in quaternary structure, it has been shown that in general, the mammalian trimeric PNPs have a higher substrate specificity and efficiency than the hexameric enzymes (6,30,31). The crystal structures of these enzymes together with biochemical and mutational studies (29,32,33) have allowed detailed mapping of the active sites for several enzymes in the PNP family and specific roles in substrate binding and catalysis have been assigned. While all of these enzymes utilize inorganic phosphate to cleave the glycosidic bond of nucleosides, key structural differences exist which account for the variation in substrate specificities.…”
Section: Substrate-induced Conformationalmentioning
confidence: 99%
“…Скорость фосфоролиза и/или синтеза аденозина на 1% меньше скорости таковой для инозина [70]. Однако, некоторые ПНФ конкурентно ингибируются аденином и/или аденозином, а, следовательно, связывают их, как например, ПНФ из клеток саркомы 180, Cellulomonas, Proteus vulgaris [67].…”
Section: коэффициенты экстинкцииunclassified